Gender equity: revealing the reality for the women of Jambi - Wiliam-de Vries, D.; Sutarti, N. (Center for International Forestry Research, 2006)
In recent years, the term ‘gender’ has become a hot discussion topic in various forums and media. Many development sectors require gender analysis as a component of a program’s implementation. However, even today, many people still equate gender with sex or even, as a narrower definition, with women. This is particularly true in regions, where gender has not yet commonly been discussed, such as Bungo and Tanjung Jabung Barat (Tanjabbar) districts, Jambi. This common idea is not surprising given that more women are adversely affected by gender inequity in the family environment and society than men. Thus, when gender is discussed, one might think that gender is identical with women’s issues.